Estimating child costs : a critical review of the underlying concepts and methods of estimation: a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey Univeristy - Perry, Bryan (Massey University, 1996)
The objectives of this research were: • to identify and examine the concepts underlying the notion of 'the costs of children' in both the New Zealand and the international literatures on the subject; and • to provide a critical account of how these costs have been estimated and an indication of the sorts of values that have been produced as a result. This study represents the 'document research' component of a larger research project which aims to produce some credible New Zealand based estimates of child costs and to provide a critical account of the rationales for State financial support for children in New Zealand in recent years. While it gives some estimates of New Zealand child costs (mainly on the basis of studies done in other countries) and is cognizant of policy implications, it is primarily a preparatory conceptual paper that supports the rest of the project. A comprehensive bibliography forms part of the report. In a recent brief review of the literature, the Office of the Commissioner for Children noted that '[t]he New Zealand research on the cost of children is sparse' (Robertson, 1994: 20). This report is a first step towards meeting the need and is designed to give the inquisitive non-expert mediated access to the vast, complex and often rather abstract literature (including the more technical papers) and to be a practical and updatable guide on the subject. It stops short of major technical discussion and exposition, but for those with more advanced mathematical and statistical skills and for those who may be working in a team with such colleagues, the study provides a solid conceptual framework and a full critical discussion of the issues raised in seeking to produce credible estimates of the cost of children.[FROM INTRODUCTION]
Keywords: New Zealand; Children -- Economic aspects; Cost and standard of living -- Econometric models